Membangun Kesadaran Pendidikan: Program Pengabdian Masyarakat dalam Meningkatkan Minat Remaja Melanjutkan Studi ke Perguruan Tinggi di Kecamatan Patebon - Himawan Raharjo, Firdaus; baity, intan; Arinatala, Almas (Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract The low motivation of adolescents to pursue higher education remains a social issue that requires serious attention. Economic limitations, lack of information, and minimal support from the surrounding environment often hinder them in planning their educational future. This community service program was carried out using a participatory-educative approach, positioning adolescents as active subjects while also involving parents, schools, and the community. The activities included seminars, socialization, mentoring, group discussions, and experience-sharing sessions with university students and alumni. The results indicated an increase in adolescents’ knowledge, motivation, and self-confidence in planning for higher education, as well as stronger social support for pursuing university studies. In the long term, the program fosters an educational culture, enhances human resource quality, and strengthens the competitiveness of young generations. Moreover, this model has the potential to be replicated in other regions with similar social conditions, making it a sustainable strategy to increase adolescent participation in higher education Keywords: Community service, higher education, youth motivation, quality of human resources.